WAT – RUSSIA – MIŁOSZ - Kopeć, Zbigniew (Porównania, 2012)
The author discusses the role which Russia played in the non-fictional output of Aleksander Wat and Czesław Miłosz. The most eminent example of such an interest is the book “My century” but also other texts. As far as the these authors’ different outlooks on Russia are concerned, they are determined by their origins, which is also emphasized by Miłosz. Aleksander Wat looks at Russia as a son of the Jewish nation who believes in communism. Miłosz looks at Russia as a leftist descendent of a noble family. For Wat, after the second world war Russia is associated first of all with totalitarianism and Poland is for him – for a short period of time – a place where life after Holocaust is possible. Miłosz in his post-war essays regards the USSR as an effect of historical necessity. The participants of a “struggle” for Russia are for him Stanisław Brzozowski and Fyodor Dostoyevsky. Miłosz, in opposition to Wat, is aware that such Polish-Polish discussions are not interesting for anybody in the West.